Measuring the Effectiveness of Suggestopedia Method in EFL Writing Class - Sardian Maharani Asnur (Jurnal Adabiyah: Humanities and Islamic Studies, 2015)
This study explores the effectiveness of suggestopedia method in EFL writing class. It also gives elaboration of activities in suggestopedia method that have proven useful in an EFL learning class. The research was conducted to the 2nd semester students of English and Literature Department at Alauddin Islamic State University of Makassar, South Sulawesi, academic year of 2014/2015. There are 15 students that became sample of the research which is selected by random sampling technique. Research shows that by suggestopedia method, students become better in writing descriptive paragraph. Through suggestopedia, students learn in an enjoyable way and without any psychological barrier that can disturb the learning process. The result also shows that the outcomes of each students are varies seeing from their post-test writing score; therefore, the writer concluded that the students got a good score because of an enjoyable learning, not because the classic music. Nevertheless, suggestopedia is a good method to develop the students’ writing ability.